The effectiveness of nutritional education on the knowledge of diabetic patients using the health belief model - Gholamreza Sharifirad; Mohammadhassan Entezari; Aziz Kamran; Leila Azadbakht (Journal of Research in Medical Sciences, 2009)
BACKGROUND: Patients have a major role in the control and treatment of type 2 diabetes. So, knowledge of different aspects of this disease especially diet therapy is very important for these patients. This study was conducted to determine the effectiveness of the Health Belief Model (HBM) on nutrition education in type 2 diabetic patients. METHOD: Eighty eight type 2 diabetic patients attending Iranian Diabetes Association seminars were randomly selected to participate in the study (44 in intervention group and 44 in control group). The intervention was consisted of two educational sessions each one for 80 minutes. Data were collected by a validated and reliable questionnaire (58 questions) before intervention and one month after intervention. RESULTS: After intervention, knowledge scores increased in the intervention group compared to the control group (Mean differences in the intervention and test group: 22.68 ± 15.90 vs - 2.27 ± 17.30, P < 0.001). Perceived susceptibility increased significantly in the intervention group compared to the control group (27.5 ± 18.5 vs 3.9 ± 17.2, P < 0.001). The result was the same for perceived severity, perceived threatened and perceived benefits (P < 0.001). In contrast perceived barriers reduced in the intervention group compared to the control diet (-14.7 ± 13.3 vs 0.9 ± 13.9, P < 0.001). In the intervention group, behavior grades increased more than control group (34.61 ± 14.93 vs -0.23 ± 8.52, P < 0.001). CONCLUSION: The efficacy of the health belief model in nutritional education to the diabetic patients was confirmed in the present study.